A Pilot Study Characterizing Factors in Adherence to Cutaneous Lupus Treatment. Issue 5 (September 2018) - Ro, Teresa; Tull, Rechelle Z.; Cardwell, Leah A.; Farhangian, Michael E.; Moustafa, Farah; Richardson, Irma; Jorizzo, Joseph L.; Feldman, Steven; Huang, William
Cutaneous lupus erythematosus (CLE) is an autoimmune skin disease that manifests as scarring, dyspigmentation, erythema, and pain. Topical corticosteroids are a mainstay of treatment. Irritation, messiness, and tediousness may deter use. Thus, nonadherence, rather than nonresponse, can result in treatment failure. Prior adherence studies were limited to systemic lupus erythematosus. We performed a single-center, open-label pilot study to assess adherence to topical medication in patients with CLE. CLE adherence to topical medications is suboptimal and declines over time. Shorter treatment duration and greater patient perception of disease severity may contribute to higher adherence. Improving adherence to existing treatments could be as or more valuable than new therapies for the disease.